2018
DOI: 10.4049/jimmunol.1800189
|View full text |Cite
|
Sign up to set email alerts
|

miR-340 Alleviates Psoriasis in Mice through Direct Targeting of IL-17A

Abstract: Th17 cell is a well-known lineage of CD4 effector Th cells that selectively produce IL-17A and play critical roles during the pathogenesis of autoimmune disease. A microRNA (miRNA) is a small noncoding RNA molecule that functions in posttranscriptional regulation of gene expression. Recently, an increasing number of studies have demonstrated that multiple miRNAs are dysregulated in patients with various autoimmune diseases and mediate autoimmune disease pathologic condition at least in part through the regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 51 publications
0
22
0
Order By: Relevance
“…miRs usually bind to the 3'UTR region on the target mRNA, causing either the degradation of the mRNA sequence or an inhibition of its translation [5]. Previous studies have evaluated the levels of miR-1266, miR-340 and miR-197, which are thought to act via IL-17A in patients with psoriasis [12][13][14][15]. In two studies, miR1266 were found to be significantly higher in plaque psoriasis patients than in healthy controls and showed a correlation with PASI, suggested that the effect of miR-1266 on the pathogenesis of psoriasis was not through a regulation of IL-17A expression but through a more upstream signaling mechanism or miR-1266 is not likely to regulate IL-17A expression directly, but may be involved in the pathogenesis of psoriasis by regulating other target molecules [12][13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…miRs usually bind to the 3'UTR region on the target mRNA, causing either the degradation of the mRNA sequence or an inhibition of its translation [5]. Previous studies have evaluated the levels of miR-1266, miR-340 and miR-197, which are thought to act via IL-17A in patients with psoriasis [12][13][14][15]. In two studies, miR1266 were found to be significantly higher in plaque psoriasis patients than in healthy controls and showed a correlation with PASI, suggested that the effect of miR-1266 on the pathogenesis of psoriasis was not through a regulation of IL-17A expression but through a more upstream signaling mechanism or miR-1266 is not likely to regulate IL-17A expression directly, but may be involved in the pathogenesis of psoriasis by regulating other target molecules [12][13].…”
Section: Discussionmentioning
confidence: 99%
“…In two studies, miR1266 were found to be significantly higher in plaque psoriasis patients than in healthy controls and showed a correlation with PASI, suggested that the effect of miR-1266 on the pathogenesis of psoriasis was not through a regulation of IL-17A expression but through a more upstream signaling mechanism or miR-1266 is not likely to regulate IL-17A expression directly, but may be involved in the pathogenesis of psoriasis by regulating other target molecules [12][13]. Bian et al have shown that miR-340 can bind specifically to the 3'UTR region of IL-17A and reduce endogenous IL-17A expression in mouse skin with psoriasis [14]. Elharrar et al reported that miR-197 expression was lower in psoriatic skin keratinocytes than in the healthy skin, suggesting that a decrease in the suppression of the IL-17A pathway may lead to an accelerated proinflammatory process [15].…”
Section: Discussionmentioning
confidence: 99%
“…Elevated miR-340 in mice lung tissue after exposure to PM 2.5 was associated with Type 1 T helper (Th1) / Type 2 T helper (Th2) cells immune imbalance [66]. In a mouse model of psoriasis, the expression of miR-340 was decreased, and treatment with miR-340 suppressed the expression of endogenous IL-17A and alleviated the clinical severity of psoriasis [67]. In conditions related to metabolic changes, circulating miR-340 was lower in maternal obesity and associated with more impaired glucose tolerance [68], and a decreased level of miR-340 was observed after a six-month high glycemic index diet [69].…”
Section: Discussionmentioning
confidence: 99%
“…miR-340 was decreased in T cells from the Imiquimod psoriasis mouse model, thus increasing the release of IL-17A. Furthermore, treatment with miR-340 alleviated the clinical severity of Imiquimod-induced psoriasis (46).…”
Section: Mirna-mediated Cytokine Targeting In Autoimmune Diseasesmentioning
confidence: 99%